Anisotropic dynamic mechanical response of tungsten fiber/Zr-based bulk metallic glass composites. (5th March 2016) - Wang, B.P.; Yu, B.Q.; Fan, Q.B.; Liang, J.Y.; Wang, L.; Xue, Y.F.; Zhang, H.F.; Fu, H.M.
Abstract: The anisotropic dynamic mechanical behavior of the W fiber/Zr-based bulk metallic glass composites (Wf /BMGCs) with different W fiber orientations ( θ f ) were investigated by split Hopkinson pressure bar (SHPB) and finite element method (FEM). The composites exhibited the most excellent mechanical properties at θ f of 0° while the poorest at θ f of 45°. The composites failed by longitudinal splitting at θ f of 0°, shearing at θ f of 45°, a mixture of shearing and splitting during 0° <  θ f  < 45° or 45° <  θ f  < 90°, and a mixture of shearing and transverse splitting at θ f of 90°. Strain rate sensitivity of the composites also varied with θ f, exhibiting positive strain rate sensitivity at θ f of 0°, 15°, 60°, and 75° ranging from the strain rate of 10 − 3 to 2.1 × 10 3  s − 1, positive strain rate sensitivity with the strain rate ranging from 10 − 3 to 10 − 2  s − 1 but negative strain rate sensitivity from 10 − 2 to 2.1 × 10 3  s − 1 at θ f of 30° and 90°, and even strain rate insensitivity at θ f of 45°. Graphical abstract: Highlights: The W fiber orientation ( θ f ) had great effect on the dynamic mechanical behavior. The composites exhibited the most excellent mechanical properties at θ f of 0°. The composites exhibited different failure modes when θ f ranged from 0° to 90°. The composites exhibited inconsistent strain rate sensitivity with different θ f .